Hubungan Jenis Kelamin Dengan Tingkat Stres Pada Remaja Siswa SMA Di Kota Kediri Tahun 2017 - Arief Hakim Ramadhani; Lucia Yovita Hendrati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: stress can be defined as a situation where the demands of a person outweigh the ability of the person that makes a lack of ability to overcome the problems they face. high school students or teenager are more susceptible to stress due to lack of ability in coping stress and solving problems. Stress can cause physiological and biological changes and can cause other diseases.Methods: The type of this research is observational analytic with cross sectional design, and using the two stage random sampling method. The respondent of this research consist of 78 people from high school student in Kediri City in 2017. The variables of this research is were sex and stres level experienced by respondents.Results: The results of data analysis using the chi-square test showed that there is no correlation between sex with stress levels (p=0,390; RR=1,272) in high school student in Kediri City in 2017.Conclusion: The conclusion of this research is that there is no correlation between sex and stress levels. The suggest from this research is give more attention to the teenager or high school student with social support from family and school environment.